IMPROVING INDONESIAN EFL STUDENTS SPEAKING SKILL THROUGH PECHA KUCHA - Angelina, Patricia (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
EFL students speaking skill at the university level is normally assessed through presentations in the teaching and learning activities. Therefore, the ability to deliver effective presentations is needed as it affects the EFL students competence in speaking. Most EFL students choose to use Microsoft PowerPoint to deliver their presentations in class. However, the additional pressure given to present in English normally causes them to include as much information as possible on their slides. They have the tendency to focus too much on the content and neglect the delivery aspect. As a result, most of the students only end up reading aloud their text-heavy slides, which often leads to boredom. Pecha Kucha is then introduced as a creative and innovative presentation format to improve EFL students speaking skill in delivering presentations. It is a simple, concise and effective presentation format which allows only twenty (20) slides that will advance automatically for 20 seconds each. The results of the study show that the use of Pecha Kucha has increased the EFL students speaking skill in delivering presentations. It is shown from the increased mean scores of the students presentation scores from before and after Pecha Kucha is used. It is also strengthened by the results of the interview on two students stating that Pecha Kucha has improved their speaking skill in delivering effective presentations in terms of the language use, speech delivery and interaction with audience.